Fit for human consumption? A qualitative survey at a Ugandan pig abattoir - Roesel, Kristina; Holmes, K.; Kungu, J.; Grace, Delia; Pezo, Danilo A.; Ouma, Emily A.; Baumann, M.P.O.; Fries, R.; Ejobi, F.; Clausen, Peter-Henning (2013)
Since 1986, the numbers of pigs in Uganda have at least quadrupled and today’s more than two million pigs are in the hands of 1.1 million households. Up to 70% of all pork is estimated to be consumed in urban and peri-urban areas, mainly through informal road-side butcheries and ‘pork joints’. In August 2012, a descriptive study was conducted at a large pig slaughter house in Kampala using methods from participatory epidemiology. Focus group discussions with members of the slaughter house management and abattoir workers as well as in-depth interviews with meat inspectors were used to assess various parameters. These included the annual supply and influencing factors; description of the slaughter process, product flow and by-product management; identification of stakeholders’ knowledge, attitudes and practices on meat hygiene and potential risk factors that could compromise the health of abattoir workers as well as end consumers. The supply of live pigs to the slaughter house has increased over the past 10 years, and numbers rise rapidly when schools fees are due, prior to festivals or in the event of a disease outbreak. Most of the pigs are supplied from the Central region followed by the eastern, northern and western regions through a well-established network of agents and traders buying from smallholder farmers. Preliminary results showed several factors that could increase the risk of occupational or foodborne diseases such as crowding of animals, insufficient separation between clean and dirty areas and the lack of electricity. The movement over long distances to a central slaughter house could have implications for public health in a country with abundant wildlife and with frequent occurrence of haemorrhagic fevers such as Ebola which can also be carried by pigs. Symptoms frequently observed in live pigs were diarrhoea, nasal discharge or skin problems including signs compatible with African swine fever. Lesions that were commonly observed in slaughtered pigs included cysts and white spots in the liver, lung congestion and ectoparasites such as fleas and mites, but the policy on condemnation of carcasses was ambiguous. The perception about who is responsible for meat hygiene is biased among members of management and staff. Further and ongoing research include the analysis of serum, tissue and faecal samples as well as an assessment of preferences and attitudes on the consumers’ end of the pig value chain in Uganda. This will eventually feed into a comprehensive risk assessment and hence identify critical control points for interventions such as training of slaughterhouse personnel or a management system that could guarantee an independent and improved meat inspection process.